Influence of the tumor microenvironment on genetic mutations in thyroid carcinoma - Lingyan Zhou; Shujian Xu; Yuwen Song; Dongqing Jiang; Shihong Chen (PLoS ONE, 2026)
In contrast to cancers with high immunotherapy responsiveness, such as lung cancer and melanoma, thyroid carcinoma (THCA) immunotherapy remains investigational. To establish a theoretical foundation for THCA immunotherapy, we investigated the association between genetic mutations and tumor microenvironment (TME) by analyzing RNA-sequencing data and somatic mutation profiles from 571 THCA samples in The Cancer Genome Atlas (TCGA) database. The ESTIMATE algorithm was first applied to calculate ImmuneScores and StromalScores. Samples were subsequently stratified into immune-high and immune-low groups, as well as stromal-high and stromal-low groups, based on median score thresholds. We then identified differentially expressed genes (DEGs) and differentially mutated genes (DMGs). Significant disparities in mutation frequencies of BRAF , NRAS , and HRAS were observed both between immune stratification groups (high vs low) and stromal stratification groups (high vs low). Correlation analysis between DMGs and clinicopathological features revealed that BRAF / NRAS expression levels were associated with THCA clinical stage. CIBERSORT computational algorithm was also used to quantify the relative abundance of tumor-infiltrating immune cells (TICs), demonstrating that 11 types of activated TICs were strongly associated with BRAF expression. Finally, we examined target DMGs expression in relation to immune checkpoint proteins (ICPs) to identify potential therapeutic targets. THCA specimens with suppressed BRAF expression demonstrated upregulated ICPs expression, indicating potential susceptibility to checkpoint blockade immunotherapy.